Struktura terytorialna diecezji lubelskiej w latach 1805-1808 - Kumor-Mielnik, Joanna (Archiwa, Biblioteki i Muzea Kościelne, 2011)
The above text continues the issues contained in the article which appeared in the previous (94) volume of this academic journal. It concerns the process of marking the boundaries of the diocese of Chełm and Lublin, which originated the diocese of Lublin in 1805. The leitmotif of this article is historical and geographical analysis of the territorial formation of the diocese of Lublin from the moment of issuing the foundation bull to the year when all the directives from the bull were implemented, and the structure of deaneries and parishes for the new diocese was completely established. The article focuses on the boundary delimitation of the diocese of Lublin and shows the problems connected with the organization of its territorial structures, and above all problems arising from the modification in the existing structure of deaneries and parishes. Cartographic presentation of the parts of diocese of Lublin and its territorial organization enables to make comparative analysis of the contents of the foundation bull for the diocese of Lublin and its later deanery and parish structure, which was legitimized after 1807. The boundary instability of the diocese of Chełm and Lublin, which was the result of the changes in the delimitation due to the partition of Poland beginning at the end of the 18th century, is the reason why this article is accompanied by a few maps, the aim of which is to illustrate each and every modification to the boundaries of the diocese of Chełm and Lublin and to show its parts along with the marked capitals of the deaneries.